Improving the texture properties and protein thermal stability of Antarctic krill (Euphausia superba) by L‐lysine marination. (7th January 2022) - Lin, Junxin; Zhang, Yuying; Li, Yiwei; Sun, Peizi; Ren, Xiang; Li, Dongmei
Abstract: BACKGROUND: The quality deterioration of Antarctic krill ( Euphausia superba ) after thermal processing limits its industrial application. This study sought to improve the texture characteristics of Antarctic krill after heat treatment through pre‐soaking using l ‐ lysine (Lys) solution and sodium tripolyphosphate (STPP). Moreover, the effects of Lys on heat‐treated Antarctic krill were explored. RESULTS: Lys significantly reduced the cooking loss and improved the texture characteristics of Antarctic krill during heat treatment. The low‐field nuclear magnetic resonance results showed that Lys reduced the water loss of Antarctic krill during heat treatment. Additionally, the surface hydrophobicity, Fourier transform infrared spectroscopy, and endogenous fluorescence spectroscopy results showed that Lys could inhibit the structural damage of Antarctic krill protein under the thermal denaturation condition and enhance the thermal stability of the protein. The scanning electron microscopy results showed that Lys could protect the structural integrity of Antarctic krill muscle fibers during heat treatment. CONCLUSION: The cooking loss in the Lys added groups was better than the sodium tripolyphosphate added group, and 2.0% Lys solution could minimize the cooking loss of Antarctic krill. The secondary and tertiary structures of the Antarctic krill protein were actively protected by Lys during heat treatment. Overall, the study will provide insights into the application of Lys in the food industry as a natural additive and an alternative to phosphate. © 2021 Society of Chemical Industry.